Possible Future Developments of Sample Surveys in Finance - Szreder, Mirosław; Gwizdała, Jerzy P. (Central and Eastern European Economic Review, 2018)
Although sample surveys do not play a primary role in research, their impact has increased recently in many areas of finance and economics. At the same time, however, new difficulties have arisen in conducting surveys and making inference on the basis of sample results. These difficulties concern not only up-to-date sampling frames and proper modes of interviewing respondents, but also the rapid increase of non-response rates, which affects the quality of outcomes. In these circumstances it seems reasonable to search for external data in order to reduce the consequences of non-sampling errors. The article presents the authors’ view on the possible use of big data as supplementary information. It also discusses some of the main challenges for survey-based research in the near future. The main conclusion is that big data will support rather than overtake surveys in finance in the years ahead.